Correlation between perceived usability of building services and indoor environmental satisfaction in retrofitted low-energy homes. (15th July 2020) - Sarran, Lucile; Hviid, Christian A.; Rode, Carsten
Abstract: Comprehensive retrofit of dwellings frequently relies on the installation of partially automated heating and mechanical ventilation systems. While energy consumption is often successfully reduced, this intrusion of complex building services into the domestic sphere may create new challenges for the occupants. Through a questionnaire distributed to 2007 households in a social housing complex undergoing energy retrofit, this work seeks to identify the link between indoor environmental satisfaction and occupants' perceived ability to use and control residential heating and ventilation technology. The response rate was 17.1% (344 houses, of which 241 were retrofitted). Occupants expressed a general satisfaction with the indoor environment in retrofitted houses. However, they also expressed difficulties to understand and operate their heating and ventilation systems. The study revealed significant correlations between the users' indoor environmental satisfaction and their perception of the usability of the building services. Nevertheless, an important share of the respondents achieved satisfactory indoor environmental quality despite living with systems with poor perceived usability. These findings point towards the hypothesis that poor usability is not an issue in normal operating conditions, but the lack of personal control becomes problematic in case of dysfunctional building services or failing building envelope. Highlights: Indoor environmental quality is largely satisfactory in retrofitted dwellings. Occupants express difficulties to operate and understand building services. Perception of IEQ and of building systems' usability are significantly correlated. They are however decoupled for high IEQ satisfaction levels.